Sigmoid Sinus Thrombosis In A Child With Unsafe Type Of Chronic Otitis Media - Chatterji, Probal; Mukherjee, Yashodeep (Nepal Journal of Neuroscience, 2024)
Correction: On 27/09/2024, Figures 1 and 2 were added to the PDF of the article. Introduction: Sigmoid sinus thrombosis, an uncommon condition, is described as a possible intra-cranial complication of both acute & chronic otitis media in standard texts. However, current medical literature mostly describes this condition in relation to acute otitis media. We are reporting a case of sigmoid sinus thrombosis as a complication of chronic otitis media. Case Report: A 10-year-old male child presented with history of long-standing right sided ear discharge and deafness. His immediate presenting complaints were swelling in the postaural region along with severe ipsilateral headache & fever for the past seven days. On clinical examination, ear findings were suggestive of chronic otitis media with cholesteatoma with mastoiditis. CT scan showed loss of architecture of the mastoid antrum and air cells with destruction of bone of mastoid cortex and complete erosion of sinus plate. MRI with contrast confirmed the presence of sigmoid sinus thrombosis. Patient was initially administered iv antibiotics and then operated. Modified radical mastoidectomy was done along with evacuation of the thrombus from the sigmoid sinus. Patient had a quick and uneventful postoperative recovery. Conclusion: Sigmoid sinus thrombosis, a rare intra-cranial complication of otitis media, can lead to several other complications including death if left untreated. Early detection and management are crucial for favourable outcome.